PENGELOLAAN PESISIR DAN KELAUTAN DALAM STUDI KASUS DAMPAK REKLAMASI PANTAI DAN TAMBANG PASIR TERHADAP EKOSISTEM LAUT DAN MASYARAKAT PESISIR - Fadel Ikrar Jamika; Fitrya Monica; Abdul Razak; Eni Kamal (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2023)
Environmental problems in Indonesia are very diverse, including those related to coastal and marine management. The main problem in coastal and marine management is that beach reclamation and sand mining activities are likely to have an impact on the environment, especially marine ecosystems and coastal communities. The existing problem of sand mining and beach reclamation has had a negative impact on coastal ecosystems and communities around the coast. The purpose of this study is to describe (1) Coastal and Marine Management in a Case Study of the Impact of Beach Reclamation and Sand Mining on Marine Ecosystems and Coastal Communities. (2) Knowing the management efforts that can be carried out in minimizing the negative impacts of sand mining and beach reclamation activities. The research location was carried out in coastal areas in Indonesia through observations from case studies of previous journals. This observation was carried out from September 2021 to December 2021. The research methodology is based on previous literature studies. The type of research used in this research is Literary Study or Library Research. The data source comes from Google Scholar and the data collection method is a qualitative method in the form of literature review (document analysis). The results of this study indicate that the existence of an overview of environmental management in the presence of mine reclamation activities has an impact on the damage caused by reclamation. The problems of sand mining and beach reclamation have had a negative impact on coastal ecosystems and communities around the coast. It also contains efforts that can be made in overcoming and minimizing environmental problems.